My own story book - Hindley, Judy; Bartelt, Robert; Goffe, Toni (New York : Starlight Editions, 1991)
A collection of seven stories featuring animals, children, and monsters.
Would you like to sleep in a hole in the ground?
Keywords: Children's stories